Brain TSPO-PET predicts later disease progression independent of relapses in multiple sclerosis - Sucksdorff M; Matilainen M; Tuisku J; Polvinen E; Vuorimaa A; Rokka J; Nylund M; Rissanen E; Airas L (United Kingdom, 2022)
Overactivation of microglia is associated with most neurodegenerative diseases. In this study we examined whether PET-measurable innate immune cell activation predicts multiple sclerosis disease progression. Activation of microglia/macrophages was measured using the 18-kDa translocator protein (TSPO)-binding radioligand 11C-PK11195 and PET imaging in 69 patients with multiple sclerosis and 18 age- and sex-matched healthy controls. Radioligand binding was evaluated as the distribution volume ratio from dynamic PET images. Conventional MRI and disability measurements using the Expanded Disability Status Scale were performed for patients at baseline and 4.1 ± 1.9 (mean ± standard deviation) years later. Fifty-one (74%) of the patients were free of relapses during the follow-up period. Patients had increased activation of innate immune cells in the normal-appearing white matter and in the thalamus compared to the healthy control group (P = 0.033 and P = 0.003, respectively, Wilcoxon). Forward-type stepwise logistic regression was used to assess the best variables predicting disease progression. Baseline innate immune cell activation in the normal-appearing white matter was a significant predictor of later progression when the entire multiple sclerosis cohort was assessed [odds ratio (OR) = 4.26; P = 0.048]. In the patient subgroup free of relapses there was an association between macrophage/microglia activation in the perilesional normal-appearing white matter and disease progression (OR = 4.57; P = 0.013). None of the conventional MRI parameters measured at baseline associated with later progression. Our results strongly suggest that innate immune cell activation contributes to the diffuse neural damage leading to multiple sclerosis disease progression independent of relapses.